PENGARUH PEMAHAMAN, MOTIVASI DAN SIKAP TERHADAP MINAT MAHASISWA MENEMPUH PENDIDIKAN PROFESI CHARTERED ACCOUNTANT (CA) PADA MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Fitri Andarin; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The world economy is heavily influenced by the growth of globalization. Free trade in within the Association of Southeast Asia Nations (ASEAN), also known as the ASEAN Economic Community (MEA) or the ASEAN Economic Community (MEA), is one impact of globalization. Type research in using certain formulas found during the testing procedure for conduct analysis as part of its quantitative methodology. Survey is a short use researchers to collect data. With Together, the variables of understanding, motivation, and attitudes about the chartered accountant (CA) profession have a positive and significant effect to student interest in chartered accountant (CA).Keywords : Understanding, Motivation, Attitudes, Chartered Accountant (CA) Profession.